STUDY OF MATRIX EFFECT IN PESTICIDE ANALYSIS BY GAS CHROMATOGRAPHY - AHUMADA F., Diego A.; GUERRERO D., Jairo A. (Vitae, 2010)
In order to study the matrix-induced chromatographic response enhancement (matrix effect), we select three different types of biotic matrices (Lactuca sativa L., Physalis peruviana L. and Solanum tuberosum) and a group of pesticides of different physicochemical characteristics including organochlorine, organophosphorus and pyrethroids pesticides. These pesticides are determined by gas chromatography by electronic microcapture detector (μECD) and nitrogen-phosphorus detector (NPD), coupled in parallel. This study evaluates the matrix effect by analysis of covariance and linear regression. There are nearly 75% of the studied pesticides which have variations in the chromatographic response compared to solvent signals. Furthermore, we notice that the nature of the matrix affect the chromatographic response of 18 of the 33 pesticides and the amount of matrix injected affects the response of only 13 pesticides.